(3x-1)(x+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3x-1=0

x+3=0

Set the first factor equal to 0.

3x-1=0

Add 1 to both sides of the equation.

3x=1

Divide each term by 3 and simplify.

Divide each term in 3x=1 by 3.

3×3=13

Cancel the common factor of 3.

Cancel the common factor.

3×3=13

Divide x by 1.

x=13

x=13

x=13

x=13

Set the next factor equal to 0.

x+3=0

Subtract 3 from both sides of the equation.

x=-3

x=-3

The final solution is all the values that make (3x-1)(x+3)=0 true.

x=13,-3

Solve Using the Square Root Property (3x-1)(x+3)=0